1 / 15

# LING 388: Language and Computers - PowerPoint PPT Presentation

LING 388: Language and Computers. Sandiway Fong 9/24 Lecture 9. Adminstrivia. Homework 2 graded class review today Homework 3 Recursion: s entential complements and relative clauses reminder: due Thursday. Homework 2 review. Question 1 : what does this do?

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.
Download Presentation

## PowerPoint Slideshow about 'LING 388: Language and Computers' - lynnea

An Image/Link below is provided (as is) to download presentation

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

### LING 388: Language and Computers

Sandiway Fong

9/24

Lecture 9

• Homework 2

• graded

• class review today

• Homework 3

• Recursion:

• sentential complements and relative clauses

• reminder: due Thursday

• Question 1: what does this do?

• Query is: for what values of variables N and Argument is the Nth argument of Term true?

• Answers:

• N=1, Argument = nn(boy)

• N=2, Argument = dt(the)

Homework 2 review

• Question 2: what does this do?

• Query is: for what values of variables Arg1 and Arg2 is arg(2,Term,Arg1),arg(2,Arg1,Arg2) true?

• Answer is:

• Arg1 = pp(in(with),np(dt(a),nn(telescope))),

• Arg2 = np(dt(a),nn(telescope))

In plain English: it picks out the 2nd sub-constituent of the 2nd sub-constituent of Term

Homework 2 review

• Question 3: give a Prolog query that picks out the word telescope from the compound term

• Query is:

Idea:

take the 2nd argument of Term, that’s the PP constituent

take the 2nd argument of PP, that’s the NP object of PP

take the 2nd argument of NP, that’s the NN head of the NP

Take the 1st argument of NN, that’s the word telescope

• Question 4: Given

devise a query using =.. that produces the complex term NP:

Answer is:

arg1

arg2

Idea:

Build term dt(the) using =.. applied to List1

Build term nn(telescope) using =.. applied to List2

Form the list [np,dt(the),nn(telescope)]

Build term np(dt(the),nn(telescope)) using =..

Homework 2 review

• Question 5: devise a query using =.. that produces the complex term PP:

• Answer is:

Idea:

Build term dt(the) using =.. applied to List1

Build term nn(telescope) using =.. applied to List2

Form the list [np,dt(the),nn(telescope)]

Build term np(dt(the),nn(telescope)) using =..

Build term in(with) using =.. applied to List3

Form the list [pp,in(with), np(dt(the),nn(telescope))]

Build term PP using =..

• Dealing with left recursion

Right Recursive Rules

• Example (right-recursive):

• nn--> a, nn.

• nn --> [bus].

• Example: big red shiny bus

• Derivation (top-down, left-to-right):

• nn

• ann

• bignn

• big ann

• big red nn

• big red ann

• big red shinynnand so on…

• Given:

• I saw the boy with a telescope (2 parses)

• Strategy:

• PP with a telescope adjoins to NP or VP:

• np(np(NP,PP)) --> np(NP), pp(PP).

• vp(vp(VP,PP)) --> vp(VP), pp(PP).

Unfortunately, this is left recursive, and Prolog will crash..

• Instead of:

• np(np(DT,NN)) --> dt(DT), nn(NN).

• np(np(NP,PP)) --> np(NP), pp(PP).

• Quick fix:

• np(np(DT,NN)) --> dt(DT), nn(NN).

• np(np(DT,NN,PP)) --> dt(DT), nn(NN), pp(PP).

• Can opt to return a left recursive parse:

• np(np(DT,NN)) --> dt(DT), nn(NN).

• np(np(np(DT,NN),PP))) --> dt(DT), nn(NN), pp(PP).

• Instead of:

• vp(vp(VBD,NP)) --> vbd(VBD), np(NP).

• vp(vp(VP,PP)) --> vp(VP), pp(PP).

• Quick fix:

• vp(vp(VBD,NP)) --> vbd(VBD), np(NP).

• vp(vp(VBD,NP,PP)) --> vbd(VBD), np(NP), pp(PP).

• Can opt to return a left recursive parse:

• vp(vp(VBD,NP)) --> vbd(VBD), np(NP).

• vp(vp(vp(VBD,NP),PP)) --> vbd(VBD), np(NP), pp(PP).

Transform left recursive into right recursive rules

Transformed example:

x --> [z], v.

v --> [y], v.

v --> [y].

x --> [z].

Language:

z

zy

zyy

zyyy …

Parses:

[x z] x(z)

[x z [v y]] x(z,v(y))

[x z [v y [v y]]] x(z,v(y,v(y)))

[x z [v y [v y [v y]]]] x(z,v(y,v(y,v(y))))

• An abstract example:

• x --> x, [y].

• x --> [z].

• Language generated by this grammar:

• z

• zy

• zyy

• zyyyand so on…

• Parses:

• [x z] x(z)

• [x [x z] y] x(x(z),y)

• [x [x [x z] y] y] x(x(x(z),y),y)

• [x [x [x [x z] y] y] y] x(x(x(z),y),y),y)

• and so on…

rewrite as

unchanged

Same language!

• right recursive version:

• x --> [z], v.

• v --> [y], v.

• v --> [y].

• x --> [z].

• add a parse:

• x(x(z,V)) --> [z], v(V).

• v(v(y,V)) --> [y], v(V).

• v(v(v)) --> [y].

• x(x(z)) --> [z].

• We can still get a left recursive parse if we add a 2nd argument to nonterminal v:

• Compare with:

• x(x(z,V)) --> [z], v(V).

• v(v(y,V)) --> [y], v(V).

• v(v(v)) --> [y].

• x(x(z)) --> [z].